Pengawasan dan Penindakan Sebagai Upaya Perlindungan Hukum Terhadap Dana Masyarakat yang Disimpan Di Lembaga Koperasi Simpan Pinjam (KSP) - Kamaluddin Pane; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. The activities of the Saving Loan Cooperative (KSP) into a special phenomenon for the past two years, the cause is a loss of Community Fund are fantastic.This is becoming a lot of questions of the extent of secuirity and a protection of Community funds that are deposited in the Institution the cooperative store, on this issue ultimately had to be returned to the proportion of the legislation and regulations, containing the entire activities of the Saving Loan Cooperative (KSP) as part of one of the forms of community economy activities which many popular varieties. As for the related legislation implementation activities KSP is Act Number 25 Of 1992 about cooperation, Act number 1 of 2013 About microfinance institutions, and regulation of the financial services authority (POJK) and ministerial regulation Cooperatives And Small And Medium Enterprises (KUKM).  The method used in this research is the juridical normative or legal research methods, that is a method by means of data collection based on the study of librarianship (library research) that is by way of examining data in the form of rules and Legislation, and the data that is retrieved by accessing the internet related to this research. The study was done with that data, so it can be compare to unknown picture of efforts to answer to the problems of the legal protection of the community's funds deposited in the Cooperative Institutions. Based on Act Number 25 year 1992 About Cooperative then convened a Community Fund activities by Cooperative Loan (KSP) is done to a limited extent. But the fact is, a lot of problematic cooperative of loan have done activities gather funds widely. In addition, according to the law number 1 Year 2013 about microfinance institutions, then should all activities KSP compulsory license, the construction and supervision of the financial services authority (OJK). And that became a problem as long as it is stored in Community Fund Cooperative Institutions (KSP) do not have a guarantor of Deposits. Keywords: legal protection, Cooperative Loan, the financial services authority, the institution of Micro finance